Acute Moderate-Intensity Strength Exercise Increases Anti-Inflammatory Cytokines in Obese Females - Adila, Fansah; Rejeki, Purwo Sri; Herawati, Lilik (Physical Education Theory and Methodology, 2023)
The study purpose was to prove the effect of acute moderate-intensity endurance and strength exercise on increasing IL-6 levels in obese females. Materials and methods. A total of 21 obese women aged 20-25 years were recruited from among university students and given two modes of acute exercise intervention, namely moderate-intensity endurance and strength exercise carried out for 35 minutes/session. Subjects were divided randomly into three groups, namely K1 (control group without intervention; n = 7), K2 (Acute moderate-intensity endurance exercise; n = 7), K3 (Acute moderate-intensity strength exercise; n = 7). ELISA was used to analyze serum IL-6 levels before and after exercise. The data analysis technique used the One-way ANOVA test and continued with the Tukey HSD post-hoc test with a significance level of 5%. Results. The results of the One-way ANOVA test showed that there was a significant difference between serum IL-6 levels after exercise and delta (Δ) in the three groups (p ≤ 0.01). The results of the Tukey HSD post-hoc test showed that there was a significant difference between serum IL-6 levels after exercise and delta (Δ) at K3 with K1 (p ≤ 0.01), K3with K2 (p ≤ 0.01), while there was no significant difference in serum IL-6 levels (p ≥ 0.05) at K2 with K1. Conclusions. Overall, our study concluded that 35 min/session of acute moderate-intensity strength exercise was effective in increasing anti-inflammatory cytokines, such as IL-6, in obese females.